Review of thirty patients with bone chondroblastoma - Slavković Slobodan; Tomić Slavko; Slavković Nemanja; Apostolović Milan (Vojnosanitetski Pregled)
Background/Aim. To analyse the results of the treatment of the patients with the diagnosis of chondroblastoma, to confirm the possible malignancy and to recommend the best and the safest method of the treatment. Methods. We reviewed the cases of 30 patients with chondroblastoma who were treated between 1975 and 2004. Data were obtained using complete medical documentation, physical examinations, radiographic findings, and the available additional diagnostic procedures. Results. We found that the proximal part of the tibia, proximal part of the humerus, and distal part of the femur were the most common sites of the tumor in 63% of the cases. The higher prevalence of chondroblastoma in male patients was found, especially in the second decade of life. The patients were treated with different surgical procedures after histologically confirmed chondroblastoma. In 1 of the patients, radiation therapy was performed because the lesion recurred, after which the malignant transformation of chondroblastoma occurred. We found two more malignant chondroblastomas, one of which had been diagnosed as a primary tumor. Seven patients had a local recurrence, one of them had a second recurrence and the malignant transformation of chondroblastoma. The only solution was a below knee amputation. Conclusion. Chondroblastoma of bone is a rare lesion with the high local recurrence rate. We emphasized the need for an adequate and rapid diagnosis, including histological verification. The treatment was strictly surgical. The basic goal of the treatment was to avoid tumor penetration into articular cavity and/or local soft tissues. Malignant chondroblastoma of bone should be treated with radical surgical resection, avoiding any adjuvant therapy.